Uranyl - PyridylAzo Resorcinol System: Uncertainty Budget Evaluation and Interference Elimination - Chandramouleeswaran, S.; Ramkumar, Jayshree (Journal of Applied Solution Chemistry and Modeling, 2023)
The spectrophotometric determination of uranyl ion with 4-(2-Pyridylazo)resorcinol (PAR) is a well known and old method. However this technique gives scope for further research in order to make it more selective as well as sensitive for uranyl ion determination. In this study, the experimental protocol has simplified as compared to previous report. An attempt to evaluate the uncertainty budget associated with the determination has been carried out. The effect of different cationic interferences has been studied and a simple method was developed to reduce the interferences.